FREQUENCY OF RAISED CARDIAC BIOMARKERS IN PATIENTS WITH COVID-19 INFECTION AND ITS ASSOCIATION WITH MORTALITY - Ahmed, Ishfaque; Syed, Beenish; Sayeed, Muneeba Ahsan; Farooqui, Fizza Jameel; Fazal, Laiba; Farman, Shaiza (Infectious Diseases Journal of Pakistan, 2022)
Background: Myocardial injury with raised Troponin levels and other cardiac biomarkers has been reported in COVID-19 and is associated with increased mortality. Data regarding clinical presentation and associated risk factors in patients with raised cardiac biomarkers in COVID-19 are limited. This study aimed to assess the frequency of myocardial injury as evidenced by raised cardiac markers in COVID-19 patients along with its association with mortality. Material and Methods: This retrospective cohort study was conducted at Sindh Infectious Diseases Hospital and Research Centre. Data for different clinical variables were collected on a structured pro forma from the medical records and clinical outcomes were seen for hospital discharge or in-hospital mortality. SPSS software (version 25.0) was used for data analysis. Categorical variables were analyzed using frequencies and percentages and compared using the x2 test or Fisher’s exact test. Continuous variables were analyzed using the mean, and median. A p-value less than 0.05 was considered statistically significant. The multivariate logistic regression model was used to see the association of mortality with independent risk factors. Results: A total of 384 patients were studied; 243 (63.3%) were males. The mean age was 64.46 years. There were 373 (97.1%) individuals with raised pro-BNP levels, and 167(43.5%) had raised troponin-I values. Also, 156(40.62%) patients had increased both troponin-I and pro-BNP levels. The most common clinical presentation was shortness of breath seen in 321 (83.6%) patients. Cytokine Release Syndrome (CRS) was seen in 169 (44%). A low ejection fraction was present in 31 (8.1%). The average mean hospital stay was 8.97 days. Two hundred and thirteen (55.46%) patients were in ICU. Mortality was seen in 159 (41.4%). Survival was significantly associated with normal troponin-I (OR: 4.8, 95%CI: 3.0-7.5, P=0.00), normal ejection fraction EF>45% (OR: 2.3, 95%CI: 1.0-5.33, P=0.034) and age more than 60 years (OR: 0.6, 95%CI: 0.38-0.94 P=0.027) while raised pro-BNP has no association with mortality (P-value <0.129). Conclusion: COVID-19 infection associated with myocardial injury as evidenced by raised cardiac enzymes and decreased ejection fraction is associated with high mortality in patients less than 60 years of age. Keywords: COVID-19, Cardiac biomarkers, Troponin I, pro-BNP, Myocardial injury